Peranan Psikologi Olahraga dalam Mengembangkan Olahraga Prestasi di Indonesia - Dimyati Dimyati (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
This article try to serve various study about the important of Sport Psychology to increase the Indonesian sport performance. Sport Psychology is needed to support the application of sport science to increase sport performnce. Various study indicated that the Sport Psychology has a real contribution and role in achieving sport performance. But in Indonesia Sport Psychology is less getting place and attention among sport practitionesr and people in higher education who has responsibility to manage and develop Psychology Scienc.e Some efforts to develop the Sport Psychology are needed to increase its contribution in increasing sport performence. Among those are : (1) growing the awareness to all component who concerned with sport performance about the important of sport psychology; and (2) improving human resource in the field of SportKey words: sport psychology, development, sport performance